PENGARUH EMPLOYER BRANDING, SOCIAL MEDIA, DAN CORPORATE REPUTATION TERHADAP INTENTION TO APPLY JOB - Pitaloka, Rafida Tri; Moko, Wahdiyat (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The number of job applicants in Indonesia far exceeds the available vacancies. This condition creates competitions among the job seekers, so prospective job providers consider several factors that can attract them or increase their intention, particularly the alumni of Universitas Brawijaya to apply. The objective of this research is to identify the effects of employer branding, social media, and corporate reputation on the intention of Universitas Brawijaya’s alumni to apply for jobs. This explanatory research elucidates the causal relationship between its dependent and independent variables through hypothesis testing. Using purposive technique, 90 people were selected as the respondents. The data analysis was performed through multiple linear regression in SPSS version 27. The results of the finding led to conclusions that employer branding, and social positively and significantly influence the intention to apply for jobs and that corporate reputation positively yet insignificantly affects the intention to apply for jobs. The results of the study can provide considerations regarding employer branding, social media, and corporate reputation in companies that Brawijaya University alumni want to apply for.